2020
DOI: 10.1155/2020/4561083
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of SIRT1 Expression in Plasma and in an In Vitro Model of Preeclampsia

Abstract: Preeclampsia (PE) is a pregnancy-specific disorder that affects 3–8% expecting mothers worldwide being one of the main causes of maternal and fetal morbidity and mortality. The search for altered circulating molecules in PE is an important target to better understand the pathophysiology of this disease. Therefore, we evaluated Sirtuin-1 (SIRT1) concentration in plasma from healthy pregnant (HP) women, gestational hypertensive women (GH), and preeclampsia women (PE) via enzyme-linked immunosorbent assay (ELISA)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 45 publications
1
18
0
Order By: Relevance
“…Notably, we found several important genes related to the pathophysiology of PE, such as matrix metallopeptidase 9 ( MMP-9 ), metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ), transforming growth factor beta receptor 2 ( TGFBR2 ), and sirtuin-1 ( SIRT1 ). Noteworthy, SIRT1 was found to be downregulated by independent analyses in PE (Viana-Mattioli et al, 2020 ). Moreover, SIRT1 was shown to have a role in regulating endothelial function, arterial remodeling, and vascular aging (Man et al, 2019 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Notably, we found several important genes related to the pathophysiology of PE, such as matrix metallopeptidase 9 ( MMP-9 ), metastasis-associated lung adenocarcinoma transcript 1 ( MALAT1 ), transforming growth factor beta receptor 2 ( TGFBR2 ), and sirtuin-1 ( SIRT1 ). Noteworthy, SIRT1 was found to be downregulated by independent analyses in PE (Viana-Mattioli et al, 2020 ). Moreover, SIRT1 was shown to have a role in regulating endothelial function, arterial remodeling, and vascular aging (Man et al, 2019 ).…”
Section: Resultsmentioning
confidence: 98%
“…However, this previous study did not explore the target genes for the miRNA 204-5p nor the mechanisms of action of these target genes. Interestingly, we found that some of the target genes for the miRNA 204-5p were also found to be downregulated by independent analyses in PE, such as brain-derived neurotrophic factor ( BDNF ) (Perucci et al, 2017 ) and SIRT1 (Viana-Mattioli et al, 2020 ). For example, SIRT1 can deacetylate histones and lead to gene silencing, and it can also regulate the function of several target proteins by deacetylation (Gomes et al, 2016 ).…”
Section: Discussionmentioning
confidence: 98%
“…Only a few studies on SIRT1 in HDPs pathogenesis are available. Reduced SIRT1 expression has been demonstrated in PE patients compared to PIH patients and healthy pregnant women, which may suggest a different pathogenetic background of PIH and PE [73]. Its decreased levels have been noticed in third-trimester placentas from patients with PE [74].…”
Section: Pathophysiology Of Preeclampsiamentioning
confidence: 97%
“…As mentioned, our results show the upregulation of placental SIRT1 by citrulline. The expression of SIRT1, an nutrient sensor, is downregulated in preeclamptic women in comparison to healthy pregnant 97 . The SIRT1-peroxisome proliferator-activated receptor gamma (PPARγ) axis is proposed to be a key player in trophoblast differentiation and placental development 44 .…”
Section: Lipid Metabolismmentioning
confidence: 98%